Insights into hominin body size, locomotion, and behavior from Early Pleistocene trackways in northern Kenya - Kevin G. Hatala; Neil T. Roach; John W. K. Harris; Purity Kiura; Emmanuel K. Ndiema; Ben Sila; David Kipkebut; Joyce Waweru; Philiphine Kisale; Apolo Alkoro Longaye; Hilary Sale; Anna K. Behrensmeyer (Proceedings of the National Academy of Sciences, 2026)
The Early Pleistocene fossils of the Koobi Fora Formation, northern Kenya, record two well-documented hominin genera, Homo and Paranthropus , preserved in the same deposits. Evidence for their ecological sympatry consists of co-occurring footprints of diverse morphologies, suggesting that Homo erectus and Paranthropus boisei were present in the same lake margin habitats over hundreds of thousands of years. Here, we report on a ~1.43 Ma fossil footprint assemblage that sheds light on Early Pleistocene hominin paleobiology and behavior. The internal morphologies of the hominin tracks align with others previously attributed to P. boisei , indicating patterns of foot morphology and locomotion different from modern Homo and more consistent with those seen in earlier Australopithecus species. However, the tracks indicate body sizes that exceed the largest skeletal estimates for P. boisei , raising the possibility that they may belong to H. erectus . Depending on their attribution, the tracks demonstrate a) larger body sizes and greater size variation in P. boisei than previously recognized, or b) levels of intraspecific anatomical and locomotor variation in H. erectus that far exceed those yet observed in modern humans or other fossil taxa. Regardless of their attribution, these tracks indicate larger than average body sizes. This supports the hypothesis that they capture a group that included multiple adult males and offers rare direct evidence for hominin social behavior. The ecological context of the tracks suggests that hominins were accessing resources in a deltaic lake margin habitat.